Quality of harvest mechanical of coffee fallen on the ground - Tavares, Tiago de Oliveira; Santinato, Felipe; Silva, Rouverson Pereira da; Voltarelli, Murilo Aparecido; Paixão, Carla Segatto Strini; Santinato, Roberto (Coffee Science - ISSN 1984-3909, 2015)
The harvest of coffee fallen on the ground is essential to reduce the losses that occurred naturally or because of the crop plant. The objective was to evaluate the operational quality of a mechanized set of coffee harvest on the soil, using the statistical process control. The evaluation of operational quality was reflected in sampling grid of 27 points, spaced 10 m in coffee row. The operation was performed in crop with load pending 90.0 ben bags of coffee. ha-1, with 15.3 ben bags of coffee. ha-1 in the soil. It was used as treatments, three rotations of PTO (444; 540 and 630 rpm), statistically distributed with nine replications. We evaluated the composition of the first material found in the soil, the amount of coffee remaining after the operation of the harvester, the collecting efficiency and the separation efficiency coffee and debris inside the machine. It was found that the amount of material to be collected may have a high variability in the distribution. The amount of this coffee in this material shows high variability, affecting the ability of gathering and separation of the machine. The increase in rotation of the PTO harvester does not increase the efficiency of gathering, but improves the separation efficiency of the coffee inside the machine.